Success and failure in establishing national physician databases: a comparison between Canada and Israel - Baruch Levi; Nadav Davidovitch; Sara Allin (Health Economics, Policy and Law)
Physician databases constitute an essential component of health workforce planning. However, while some countries have established functioning national physician databases, others have failed to do so. We compared the healthcare systems of two technologically and economically developed countries, Canada and Israel, which represent cases of respective success and failure in establishing physician databases. A comparative analysis was conducted using a historical-institutionalist approach to examine contemporary health policy outcomes. White papers, studies on healthcare human resources, and reports by professional committees were examined to explore the aims, interests, positions, and actions of stakeholders. In Canada, state–medical profession cooperation, deep-rooted in a longstanding regulatory bargain between the two parties, has facilitated the creation and management of physician databases, albeit limited and in need of urgent improvement, on national and jurisdictional levels. The lack of such regulatory arrangement coupled with enduring conflicted relations between stakeholders due to particular historical developments have hindered the development of an Israeli equivalent database so far. Finally, health policy outcomes may be explained against the backdrop of broader political, governance, and organisational contexts. How medical organisations respond to governmental healthcare initiatives is heavily influenced by their institutional position vis-à-vis the state, shaped by historical processes and regulatory arrangements.